Nine-Tenths of the Law: Enduring Dispossession in Indonesia - Tuslian, Widya Naseva (UI Scholars Hub, 2021)
In many developing countries, land ownership is something less established and not backed by long-standing legal protection as opposed to the developed countries. Indonesia is a case in point of those developing countries. In Indonesia, the struggle over land ownership has been something at all times. The conflicts over land ownership persist and develop alongside the times, political, and regime changes until the present day. Moreover, in the context of legal and institutional pluralism with multi-layers of rules and jurisdictions like in Indonesia, a claim over land can be made by many actors, which involves many authorities that govern it. Additionally, colonialism as a historical context adds another layer of intricacies of land conflicts and claims in Indonesia.